ZrO2 coated SiO2 supported nickel catalyst as well as preparation method and application thereof
By coating the SiO2 material as a support, the existing catalysts have been solved, and the existing catalysts have been effectively methanated and the stability is maintained during long-term operation.
Patent Information
- Application Number
- CN202411678317.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-11
AI Technical Summary
The existing CO2 methanation catalysts have low activity and poor stability, especially the ability to activate CO2 at low temperatures is insufficient, and the Ni-based catalysts are prone to sintering during the reaction.
ZrO2 is used to coat SiO2 materials as carrier and acetic acid as buffer to inhibit the rapid precipitation of Zr4+, so that ZrO2 is uniformly deposited on the SiO2 surface, increase the specific surface area, and ensure the electrostatic attraction of Zr(OH)4 and SiO2 by appropriately adjusting the pH value and Zr/Si ratio, so that ZrO2 is uniformly coated on the SiO2 surface.
The specific surface area and activity of the catalyst were significantly improved, the low-temperature activity and stability of the catalyst were enhanced, and the CO2 methanation reaction conversion rate could reach 97%, and there was no obvious inactivation in the 200-hour stability test.
Smart Images

Figure CN119793474A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and specifically relates to a catalyst with a ZrO2-coated SiO2 material as a carrier and a preparation method thereof, and its application in the fields of CO2 methanation and Fischer-Tropsch tail gas methanation. Background Art
[0002] Contemporary society's dependence on fossil fuels has led to large-scale emission of CO2 as a greenhouse gas, which can lead to serious environmental problems and climate change. In order to solve this problem and achieve the goal of carbon neutrality, it is necessary to develop renewable energy utilization technologies to reduce the use of fossil fuels, as well as develop carbon capture, utilization and storage technologies to reduce carbon emissions. Among them, CO2 methanation as a promising CO2 utilization technology has received widespread attention.
[0003] CO2 methanation can convert carbon dioxide into useful chemicals, thereby reducing the concentration of carbon dioxide in the atmosphere, which is of great significance for mitigating the greenhouse effect and protecting the environment. At the same time, as a clean energy source, the amount of CO2 produced by the combustion of methane is much lower than that of traditional fossil fuels such as coal and oil. Therefore, the methane produced from CO2 will not significantly increase the CO2 content in the atmosphere during the combustion process. Secondly, CO2 methanation technology can couple renewable energy with chemical energy to realize the conversion of non-carbon energy into chemical energy. Through the electrolysis of water to produce hydrogen technology, the electricity generated by renewable energy can be converted into hydrogen, and then reacted with CO2 to produce methane, thereby realizing the conversion and storage of renewable energy; at the same time, CO2 hydrogenation to produce methane can be regarded as a long-term energy storage technology, which can store hydrogen when it is not needed, and release hydrogen through the cracking or reforming reaction of methane when needed. This energy storage method is efficient, safe and economical, providing strong support for the widespread application of hydrogen energy.
[0004] Fischer-Tropsch synthesis is a process that uses synthesis gas (a mixture of carbon monoxide and hydrogen) as a raw material to synthesize liquid hydrocarbons or hydrocarbons in the presence of a catalyst and appropriate conditions. The tail gas contains valuable gases such as unreacted carbon monoxide (CO) and hydrogen (H2), as well as a large amount of CO2. If it is converted into methane (CH4) through a methanation reaction, it can reduce CO2 emissions while achieving effective utilization of resources in the tail gas.
[0005] At present, the catalysts reported for CO2 methanation are catalysts with metals such as Ru, Pt, Pd, Rh, Ni, Co, and Fe as active components. Among them, noble metal catalysts such as Ru and Rh have excellent performance and good resistance to carbon deposition, but their high prices limit their industrial applications. Ni-based catalysts have relatively high activity and selectivity, are inexpensive, and are easily available, so they have the potential for industrial application and are widely concerned by researchers. However, there are still some problems with Ni-based catalysts that limit their industrial application. On the one hand, since CO2 molecules are very stable and belong to inert compounds, the carbon atoms in them are in the highest oxidation state and are difficult to activate at low temperatures, so improving the low-temperature activity of the catalyst is a key issue that needs to be addressed; on the other hand, CO2 methanation is a highly exothermic reaction, and Ni-based catalysts have the problem of easy sintering of active metals during the reaction.
[0006] The physicochemical properties of the carrier have a significant impact on the catalytic performance of the catalyst. The carriers for CO2 methanation mainly include SiO2, Al2O3, ZrO2, TiO2, CeO2, etc. Among them, SiO2, as a conventional carrier, is cheap, easy to obtain, and has a large specific surface area. However, its surface does not have active adsorption sites, is chemically inert, and does not work well in the CO2 methanation reaction. Ni / Al2O3 catalysts have been widely studied due to their good activity and mature technology. However, the main problem is that the loading is too high, and sintering is prone to occur under long-term high-temperature operation, which accelerates the deactivation of the catalyst; and because the interaction between Ni and Al2O3 is too strong, NiAl2O4 spinel phase is easily formed, resulting in the loss of active components. Reducible carriers such as ZrO2, TiO2, and CeO2 have abundant chemical adsorption sites on the surface, which is very beneficial to improving the low-temperature activity of the methanation reaction. Among them, the catalyst with ZrO2 as the carrier exhibits excellent methanation activity. However, compared with conventional carriers, pure ZrO2 prepared by conventional methods has a lower specific surface area, which is not conducive to improving the catalyst activity. Summary of the invention
[0007] The purpose of the present invention is to increase the specific surface area of ZrO2 carrier, overcome the problems of low activity and poor stability of existing CO2 methanation catalysts, provide a catalyst with ZrO2 coated SiO2 material as carrier and a preparation method thereof, utilize the high specific surface area of SiO2, use acetic acid as a buffer, inhibit the Zr in the solution 4+ The Zr(OH)4 precipitate is formed quickly, and ZrO2 is uniformly deposited on the SiO2 surface, which solves the problem of small specific surface area of pure ZrO2 carrier and promotes the activation of ZrO2 to CO2; its loaded Ni is used as a catalyst for CO2 methanation reaction, showing high activity and good stability. In addition, it is applied to Fischer-Tropsch tail gas methanation, showing excellent performance and promoting the resource utilization of tail gas.
[0008] According to one aspect of the present invention, there is provided a ZrO2-coated SiO2-supported nickel catalyst, which is composed of Ni-MO x / SiO2@ZrO2; where: SiO2@ZrO2 is ZrO2 coated SiO2 material, used as a catalyst carrier; SiO2:ZrO2 in SiO2@ZrO2 is in a mass ratio of SiO2:1:(0.2-0.8); Ni is the active component of the catalyst, MO x MO is an additive added to the catalyst. x It is at least one of La2O3, CeO2, MgO, and CaO.
[0009] Furthermore, the mass fraction of Ni in the catalyst is 5 to 25%.
[0010] Furthermore, according to the molar ratio, Ni:MO x =1:(0~0.3).
[0011] According to another aspect of the present invention, a method for preparing the above-mentioned ZrO2-coated SiO2-supported nickel catalyst is provided, comprising the following process:
[0012] (1) dissolving zirconium nitrate in deionized water, adding glacial acetic acid and stirring to obtain a solution;
[0013] (2) adding fumed silica to the solution obtained in step (1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution;
[0014] (3) slowly adding aqueous ammonia to the mixed solution obtained in step (2) until the pH value is 5.5 to 6.4, and then aging at a temperature of 60 to 90° C. to obtain a solid-liquid mixture;
[0015] (4) centrifuging the solid-liquid mixture obtained in step (3) and drying the obtained solid;
[0016] (5) calcining the dried solid in step (4) at 500-700° C. to obtain SiO2@ZrO2;
[0017] (6) nickel nitrate, the corresponding nitrate of the auxiliary agent and citric acid are prepared into an aqueous solution, and the prepared aqueous solution is added dropwise to the SiO2@ZrO2 carrier obtained in step (5) by equal volume impregnation, and the mixture is sealed and allowed to stand at a temperature of 60 to 90° C., and dried to obtain a dried product;
[0018] (7) calcining the dried product obtained in step (6) at 500-700° C. to obtain a catalyst precursor;
[0019] (8) introducing reducing gas to reduce the catalyst precursor obtained in step (7), the reduction temperature being 450 to 700° C.; obtaining the catalyst Ni-MOx / SiO2@ZrO2.
[0020] Furthermore, in the solution obtained in step (1), the concentration of zirconium nitrate is 0.05 to 0.20 mol / L, and the concentration of glacial acetic acid is 0.6 to 2.4 mol / L.
[0021] Furthermore, the mass concentration of silicon dioxide in the mixed solution of step (2) is 15.4 to 92.4 g / L.
[0022] Furthermore, the feeding rate of aqueous ammonia in step (3) is 5 to 20 mL / h.
[0023] Furthermore, the aging time in step (3) is 6-24 hours.
[0024] Furthermore, the drying in step (4) is carried out in an oven at 60-120° C. for 6-24 hours.
[0025] Furthermore, in step (6), the nitrate corresponding to the auxiliary agent is at least one of lanthanum nitrate, cerium nitrate, magnesium nitrate and zirconium nitrate.
[0026] Furthermore, in step (6), the molar ratio of nickel nitrate to the corresponding nitrate of the auxiliary agent is 1:(0-0.3).
[0027] Furthermore, in step (6), the molar ratio of the sum of nickel nitrate and the corresponding nitrate of the auxiliary agent to citric acid is 1:(1-3).
[0028] Furthermore, in step (6), the sealing standing time is 12 to 48 hours.
[0029] Furthermore, in step (6), the step of standing at a temperature of 60 to 90° C. is performed by placing the mixture in an oven for 5 to 7 hours.
[0030] Furthermore, the drying in step (6) is carried out in an oven at 100-150° C. for 6-24 hours.
[0031] Furthermore, in step (5) and step (7), the calcination time is 2 to 6 hours, and the heating rate is 1 to 10° C. / min.
[0032] Furthermore, in step (8), 10 to 30 mL / min of reducing gas is introduced, the heating rate is 1 to 10° C. / min, and the reduction time is 1 to 3 h.
[0033] Furthermore, in step (8), the reducing gas is hydrogen, or carbon monoxide, or a mixture of at least one of hydrogen and carbon monoxide and an inert gas; wherein the volume percentage of the inert gas in the mixed gas atmosphere is 1% to 99%.
[0034] According to another aspect of the present invention, there is provided a ZrO2-coated SiO2-supported nickel catalyst for use in a CO2 methanation reaction or a Fischer-Tropsch tail gas methanation reaction.
[0035] Further, the catalyst is added to a fixed bed reactor, and the catalyst is introduced into the reactor at a volume space velocity of 5000-60000 mL / (g cat h) introducing carbon dioxide and hydrogen, wherein the molar ratio of carbon dioxide to hydrogen is 1:(1-5), to obtain the target product methane.
[0036] Further, the catalyst is added to a fixed bed reactor, and the catalyst is introduced into the reactor at a volume space velocity of 5000-60000 mL / (g cat h) introducing Fischer-Tropsch tail gas to obtain the target product methane.
[0037] Furthermore, the composition of the Fischer-Tropsch tail gas may be H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7.
[0038] The beneficial effects of the present invention are:
[0039] (I) The ZrO2-coated SiO2-supported nickel catalyst of the present invention utilizes the high specific surface area of gas-phase SiO2 to uniformly deposit ZrO2 on the surface of SiO2. The prepared ZrO2-coated SiO2 material has a surface area of up to 130 m 2 The specific surface area of Ni-based catalysts prepared with it as a carrier can reach 137 m 2 / g, overcoming the disadvantage of low specific surface area of ZrO2.
[0040] (ii) The method for preparing a ZrO2-coated SiO2-supported nickel catalyst of the present invention adjusts the pH value, Zr / Si ratio, solution concentration, etc. so that Zr(OH)4 in the solution is positively charged and SiO2 is negatively charged. The two are attracted by electrostatic attraction to wrap Zr(OH)4 nanoparticles on the surface of SiO2. After calcination, a ZrO2-coated SiO2 (SiO2@SiO2) carrier is obtained.
[0041] (III) The ZrO2-coated SiO2-supported nickel catalyst prepared by the present invention is applied to the CO2 methanation reaction and can show good activity and stability. The CO2 methanation reaction conversion rate can reach 97%, and the stability test shows no deactivation after 200 hours, which has certain industrial prospects.
[0042] (IV) The ZrO2-coated SiO2-supported nickel catalyst prepared by the present invention is applied to the Fischer-Tropsch tail gas methanation reaction and can show good activity. The CO conversion rate can reach 100%, and the CO2 methanation reaction conversion rate can reach 99%. Both CO and CO2 are converted into methane, which has the prospect of industrial Fischer-Tropsch tail gas treatment and resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is the zeta potential of SiO2@ZrO2, and SiO2 and ZrO2 at different pH values in Example 1.
[0044] Figure 2 This is the X-ray diffraction (XRD) pattern of SiO2@ZrO2 in Example 1, after catalyst calcination, reduction and stabilization.
[0045] Figure 3 This is the STEM image and element distribution map of SiO2@ZrO2 in Example 1.
[0046] Figure 4 These are the locally enlarged STEM images and line scan images of SiO2@ZrO2 in Example 1.
[0047] Figure 5 These are the nitrogen adsorption-desorption isotherms and specific surface areas of SiO2@ZrO2 and Ni / SiO2@ZrO2 in Example 1.
[0048] Figure 6 These are the stability test results of the catalyst in Example 1 in the CO2 methanation reaction. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0050] Example 1
[0051] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0052] 2) Adding fumed silica to the solution obtained in step 1), stirring with ultrasound until the fumed silica is completely dispersed, to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L.
[0053] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0054] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0055] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0056] The zeta potential of SiO2@ZrO2, SiO2 and ZrO2 at different pH values was tested. Before the test, the samples were dispersed with deionized water and prepared into dispersion suspensions with different pH values using 1 mol / L ammonia water and nitric acid. Figure 1 The zeta potential at different pH values shows that the isoelectric points of SiO2@ZrO2, SiO2 and ZrO2 are 6.2, 2.0 and 6.5 respectively. The isoelectric point of SiO2@ZrO2 is very close to that of ZrO2, which is very different from the isoelectric point of SiO2, indicating that the outer surface of the prepared SiO2@ZrO2 is mainly ZrO2, and ZrO2 is well coated on the surface of SiO2.
[0057] Depend on Figure 2 The XRD spectrum shows that the ZrO2 grains in SiO2@ZrO2 are very small, with an average grain size of about 4 nm. Figure 3 From the element distribution diagram, we can see that the Zr element on the surface of SiO2@ZrO2 is evenly dispersed, which is in line with expectations. Figure 4 As shown, it can be observed that the outer side of the particles is mainly composed of Zr elements, and the inner side is mainly composed of Si elements, indicating that SiO2@ZrO2 has ZrO2 as the shell and SiO2 as the core.
[0058] The specific surface area of SiO2@ZrO2 was tested: first, the sample was vacuum degassed at 300°C for 4 h; after removing the surface adsorbed substances, N2 was adsorbed in the relative pressure range of 0.05-0.30 to obtain the adsorption-desorption isotherm; the specific surface area (S BET ) is determined by the BET equation. Figure 5 It can be seen that its specific surface area reaches 130m 2 / g.
[0059] 6) Weigh the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1.2, with a nickel nitrate concentration of 1.3 mol / L; add the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, seal and let stand for 24 hours, place in an oven at 80°C for 6 hours, and then dry at 120°C overnight to obtain a dried product.
[0060] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0061] from Figure 2 The NiO crystal phase can be observed in the XRD spectrum. Figure 5 It can be seen that its specific surface area reaches 137m 2 / g.
[0062] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0063] 9) CO2 and hydrogen at a molar ratio of 1:4 were introduced into the reactor for CO2 methanation test.
[0064] At a volume space velocity of 60000 mL / (g cat h), under the condition of 0.1MPa pressure, the catalytic performance of CO2 hydrogenation methanation reaction is as follows: at 200℃, the CO2 conversion rate is 5.4%, and the CH4 selectivity is 100%; at 350℃, the CO2 conversion rate is 60.5%, and the CH4 selectivity is 100%; at 450℃, the CO2 conversion rate is 81.5%, and the CH4 selectivity is 99.3%.
[0065] At a volume space velocity of 15000 mL / (g cat h), under the condition of 3Mpa pressure, the catalytic performance of CO2 hydrogenation methanation reaction is as follows: at 200°C, the CO2 conversion rate is 9.8%, and the CH4 selectivity is 100%; at 300°C, the CO2 conversion rate is 79.0%, and the CH4 selectivity is 100%; at 450°C, the CO2 conversion rate is 94.9%, and the CH4 selectivity is 100%.
[0066] At a volume space velocity of 5000 mL / (g cath), under the condition of 5Mpa pressure, the catalytic performance of CO2 hydrogenation methanation reaction is as follows: at 200℃, the CO2 conversion rate is 13.6%, and the CH4 selectivity is 100%; at 350℃, the CO2 conversion rate is 81.4%, and the CH4 selectivity is 100%; at 450℃, the CO2 conversion rate is 96.9%, and the CH4 selectivity is 100%.
[0067] The stability of the catalyst was tested at 500°C. The reaction conditions were: the reaction gas composition was H2:CO2=4:1, the reaction pressure was 3MPa, the temperature was 550°C, the reaction space velocity was 15000mL / (g cat h). By Figure 6 It can be seen that the catalyst has no tendency of activity decline within 200 h and has excellent stability.
[0068] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, CO2 conversion rate is 8.9%, CO conversion rate is 50.2%; at 300℃, CO2 conversion rate is 78.4%, CO conversion rate is 100%; at 400℃, CO2 conversion rate is 94.9%, CO conversion rate is 100%. At 500℃, CO2 conversion rate is 96.5%, CO conversion rate is 98.2%.
[0069] Example 2
[0070] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.05 mol / L, and the concentration of glacial acetic acid is 2.4 mol / L.
[0071] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 15.4 g / L;
[0072] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0073] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 60° C. overnight.
[0074] 5) The dried solid obtained in step 4) was calcined at 500° C. for 2 h to obtain SiO2@ZrO2, with a heating rate of 1° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0075] 6) Weigh the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1.2, with a nickel nitrate concentration of 1.3 mol / L; add the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, seal and let stand for 12 hours, place in an oven at 60°C for 7 hours, and then dry at 100°C overnight to obtain a dried product;
[0076] 7) The dried product obtained in step 6) was calcined at 500° C. for 2 h at a heating rate of 1° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0077] 8) The obtained catalyst precursor was placed in a reactor and reduced at 450°C for 1 h in H2 with a flow rate of 10 mL / min and a heating rate of 1°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0078] 9) Under the condition of 3 MPa pressure, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was carried out by introducing CO2 and hydrogen at a molar ratio of 1:4.
[0079] Under the above conditions, the catalytic performance of CO2 hydromethanation reaction is as follows:
[0080] At 200°C, the CO2 conversion rate is 10.3%; at 350°C, the CO2 conversion rate is 86.6%; at 450°C, the CO2 conversion rate is 94.4%, and the CH4 selectivity at the above temperatures is 100%.
[0081] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 9.7%, and the CO conversion rate is 51.4%; at 300℃, the CO2 conversion rate is 84.7%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 93.8%, and the CO conversion rate is 100%.
[0082] Example 3
[0083] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.20 mol / L, and the concentration of glacial acetic acid is 0.6 mol / L.
[0084] 2) Adding fumed silica to the solution obtained in step 1), stirring with ultrasound until the fumed silica is completely dispersed, to obtain a mixed solution, wherein the mass concentration of the fumed silica is 61.6 g / L.
[0085] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0086] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 120° C. overnight.
[0087] 5) The dried solid obtained in step 4) was calcined at 700° C. for 6 h to obtain SiO2@ZrO2, with a heating rate of 10° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0088] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1.2, the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 48 hours, placing in an oven at 90°C for 5 hours, and then drying at 150°C overnight to obtain a dried product;
[0089] 7) The dried product obtained in step 6) was calcined at 700° C. for 6 h at a heating rate of 10° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0090] 8) The obtained catalyst precursor was placed in a reactor and reduced at 700°C for 3 h in H2 with a flow rate of 30 mL / min and a heating rate of 10°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0091] 9) Under the condition of 3 MPa pressure, the reactor was charged with a volume space velocity of 15000 mL / (g cat h) CO2 methanation test was carried out by introducing CO2 and hydrogen at a molar ratio of 1:4.
[0092] Under the above conditions, the catalytic performance of CO2 hydromethanation reaction is as follows:
[0093] At 200°C, the CO2 conversion rate is 7.6%; at 350°C, the CO2 conversion rate is 83.9%; at 450°C, the CO2 conversion rate is 93.7%, and the CH4 selectivity at the above temperatures is 100%.
[0094] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 7.4%, and the CO conversion rate is 50.1%; at 300℃, the CO2 conversion rate is 81.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 94.1%, and the CO conversion rate is 100%.
[0095] Example 4
[0096] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0097] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 92.4 g / L;
[0098] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0099] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0100] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.2.
[0101] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1.2, the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80°C for 6 hours, and then drying at 120°C overnight to obtain a dried product;
[0102] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0103] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0104] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0105] At 200°C, the CO2 conversion rate is 7.4%; at 350°C, the CO2 conversion rate is 82.9%; at 450°C, the CO2 conversion rate is 92.4%, and the CH4 selectivity at the above temperatures is 100%.
[0106] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 6.9%, and the CO conversion rate is 52.2%; at 300℃, the CO2 conversion rate is 80.7%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 93.7%, and the CO conversion rate is 100%.
[0107] Example 5
[0108] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0109] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 23.1 g / L;
[0110] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0111] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0112] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.8.
[0113] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1.2, the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80°C for 6 hours, and then drying at 120°C overnight to obtain a dried product;
[0114] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0115] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0116] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0117] At 200°C, the CO2 conversion rate is 8.6%; at 350°C, the CO2 conversion rate is 90.3%; at 450°C, the CO2 conversion rate is 93.8%, and the CH4 selectivity at the above temperatures is 100%.
[0118] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 7.7%, and the CO conversion rate is 53.2%; at 300℃, the CO2 conversion rate is 85.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 92.6%, and the CO conversion rate is 100%.
[0119] Example 6
[0120] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0121] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0122] 3) Slowly add aqueous ammonia to the mixed solution obtained in step 2) until the pH value is 5.5, the feed rate of aqueous ammonia is 5 mL / h, and age at 70° C. overnight to obtain a solid-liquid mixture.
[0123] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 60° C. overnight.
[0124] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0125] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:3, the nickel nitrate concentration is 0.4 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 60° C. for 7 hours, and then drying at 100° C. overnight to obtain a dried product;
[0126] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0127] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 5%.
[0128] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0129] At 200°C, the CO2 conversion rate is 2.8%; at 350°C, the CO2 conversion rate is 78.6%; at 450°C, the CO2 conversion rate is 89.2%, and the CH4 selectivity at the above temperatures is 100%.
[0130] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 2.5%, and the CO conversion rate is 40.6%; at 300℃, the CO2 conversion rate is 69.6%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 84.9%, and the CO conversion rate is 100%.
[0131] Example 7
[0132] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0133] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0134] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH value is 6.4, the feeding rate of ammonia water is 20 mL / h, and the mixture is aged at 90° C. overnight to obtain a solid-liquid mixture.
[0135] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 120° C. overnight.
[0136] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0137] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: citric acid = 1:1, the nickel nitrate concentration is 2.2 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 90° C. for 7 hours, and then drying at 150° C. overnight to obtain a dried product;
[0138] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO / SiO2@ZrO2.
[0139] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni / SiO2@ZrO2 with a Ni mass fraction of 25%.
[0140] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0141] At 200°C, the CO2 conversion rate is 10.3%; at 350°C, the CO2 conversion rate is 86.2%; at 450°C, the CO2 conversion rate is 94.1%, and the CH4 selectivity at the above temperatures is 100%.
[0142] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 9.7%, and the CO conversion rate is 48.9%; at 300℃, the CO2 conversion rate is 82.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 93.3%, and the CO conversion rate is 100%.
[0143] Example 8
[0144] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0145] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0146] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0147] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0148] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0149] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: magnesium nitrate: citric acid = 1: 0.125: 1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise onto the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0150] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-MgO / SiO2@ZrO2.
[0151] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-MgO / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0152] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0153] At 200°C, the CO2 conversion rate is 14.7%; at 350°C, the CO2 conversion rate is 89.7%; at 450°C, the CO2 conversion rate is 95.1%, and the CH4 selectivity at the above temperatures is 100%.
[0154] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 14.3%, and the CO conversion rate is 53.2%; at 300℃, the CO2 conversion rate is 83.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 96.8%, and the CO conversion rate is 100%.
[0155] Example 9
[0156] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0157] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0158] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0159] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0160] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0161] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: calcium nitrate: citric acid = 1: 0.125: 1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0162] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CaO / SiO2@ZrO2.
[0163] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-CaO / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0164] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0165] At 200°C, the CO2 conversion rate is 15.2%; at 350°C, the CO2 conversion rate is 94.2%; at 450°C, the CO2 conversion rate is 96.5%, and the CH4 selectivity at the above temperatures is 100%.
[0166] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 14.9%, and the CO conversion rate is 54.1%; at 300℃, the CO2 conversion rate is 85.6%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 97.7%, and the CO conversion rate is 100%.
[0167] Example 10
[0168] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0169] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0170] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0171] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0172] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0173] 6) Weighing the required drugs to prepare aqueous solution in a molar ratio of nickel nitrate: lanthanum nitrate: citric acid = 1:0.125:1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80°C for 6 hours, and then drying at 120°C overnight to obtain a dried product;
[0174] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-La2O3 / SiO2@ZrO2.
[0175] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2 h in H2 with a flow rate of 20 mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-La2O3 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0176] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0177] At 200°C, the CO2 conversion rate is 20.9%; at 350°C, the CO2 conversion rate is 95.6%; at 450°C, the CO2 conversion rate is 97.1%, and the CH4 selectivity at the above temperatures is 100%.
[0178] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 16.7%, and the CO conversion rate is 54.7%; at 300℃, the CO2 conversion rate is 91.8%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 99.0%, and the CO conversion rate is 100%.
[0179] Embodiment 11
[0180] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0181] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0182] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0183] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0184] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0185] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: citric acid = 1: 0.125: 1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0186] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2 / SiO2@ZrO2.
[0187] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2h in H2 with a flow rate of 20mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-CeO2 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0188] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0189] At 200°C, the CO2 conversion rate is 15.6% and the CH4 selectivity is 100%; at 350°C, the CO2 conversion rate is 92.9% and the CH4 selectivity is 100%; at 450°C, the CO2 conversion rate is 96.9% and the CH4 selectivity is 100%.
[0190] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 13.9%, and the CO conversion rate is 53.2%; at 300℃, the CO2 conversion rate is 88.3%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 97.3%, and the CO conversion rate is 100%.
[0191] Example 12
[0192] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0193] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0194] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0195] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0196] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0197] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: lanthanum nitrate: citric acid = 1:0.125:0.125:1.5, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80°C for 6 hours, and then drying at 120°C overnight to obtain a dried product;
[0198] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2-La2O3 / SiO2@ZrO2.
[0199] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2h in H2 with a flow rate of 20mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-CeO2-La2O3 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0200] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0201] At 200°C, the CO2 conversion rate is 26.2% and the CH4 selectivity is 100%; at 350°C, the CO2 conversion rate is 95.5% and the CH4 selectivity is 100%; at 450°C, the CO2 conversion rate is 97.1% and the CH4 selectivity is 100%.
[0202] 10) Under the condition of 0.1 MPa pressure, the reactor was charged with a volume space velocity of 5000 mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 12.4%, and the CO conversion rate is 41.6%; at 300℃, the CO2 conversion rate is 81.1%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 80.4%, and the CO conversion rate is 100%.
[0203] Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, CO2 conversion rate is 20.4%, CO conversion rate is 59.3%; at 300℃, CO2 conversion rate is 91.1%, CO conversion rate is 100%; at 400℃, CO2 conversion rate is 99.0%, CO conversion rate is 100%. At 500℃, CO2 conversion rate is 97.1%, CO conversion rate is 98.4%
[0204] Under the condition of 5 MPa pressure, the reactor was charged with a volume space velocity of 60000 mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 17.2%, and the CO conversion rate is 56.4%; at 300℃, the CO2 conversion rate is 89.5%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 98.6%, and the CO conversion rate is 100%.
[0205] Embodiment 13
[0206] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0207] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0208] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0209] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0210] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0211] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: citric acid = 1: 0.04: 1.248, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0212] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2 / SiO2@ZrO2.
[0213] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2h in H2 with a flow rate of 20mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-CeO2 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0214] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0215] At 200°C, the CO2 conversion rate is 12.1%; at 350°C, the CO2 conversion rate is 91.2%; at 450°C, the CO2 conversion rate is 95.7%, and the CH4 selectivity at the above temperatures is 100%.
[0216] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 10.9%, and the CO conversion rate is 53.2%; at 300℃, the CO2 conversion rate is 86.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 97.0%, and the CO conversion rate is 100%.
[0217] Embodiment 14
[0218] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0219] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0220] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0221] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0222] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0223] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: citric acid = 1:0.3:1.56, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80°C for 6 hours, and then drying at 120°C overnight to obtain a dried product;
[0224] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2 / SiO2@ZrO2.
[0225] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2h in H2 with a flow rate of 20mL / min and a heating rate of 2°C / min to obtain a catalyst Ni-CeO2 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0226] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0227] At 200°C, the CO2 conversion rate is 10.2%; at 350°C, the CO2 conversion rate is 90.4%; at 450°C, the CO2 conversion rate is 95.0%, and the CH4 selectivity at the above temperatures is 100%.
[0228] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 9.7%, and the CO conversion rate is 50.1%; at 300℃, the CO2 conversion rate is 84.6%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 96.8%, and the CO conversion rate is 100%.
[0229] Embodiment 15
[0230] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0231] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0232] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0233] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0234] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0235] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: citric acid = 1: 0.125: 1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0236] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2 / SiO2@ZrO2.
[0237] 8) The obtained catalyst precursor was placed in a reactor and reduced at 600°C for 2h in CO with a flow rate of 10mL / min and a heating rate of 1°C / min to obtain a catalyst Ni-CeO2 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0238] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0239] At 200°C, the CO2 conversion rate is 12.3%; at 350°C, the CO2 conversion rate is 90.1%; at 450°C, the CO2 conversion rate is 95.7%, and the CH4 selectivity at the above temperatures is 100%.
[0240] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10:C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 11.5%, and the CO conversion rate is 52.4%; at 300℃, the CO2 conversion rate is 88.7%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 97.7%, and the CO conversion rate is 100%.
[0241] Example 16
[0242] 1) Dissolve zirconium nitrate in deionized water, add glacial acetic acid, and stir to obtain a solution, wherein the concentration of zirconium nitrate in the solution is 0.15 mol / L, and the concentration of glacial acetic acid is 1.8 mol / L.
[0243] 2) adding fumed silica to the solution obtained in step 1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution, wherein the mass concentration of the fumed silica is 46.2 g / L;
[0244] 3) Slowly drop ammonia water into the mixed solution obtained in step 2) until the pH is 6, the ammonia water feed rate is 10 mL / h, and the mixture is aged at 60° C. overnight to obtain a solid-liquid mixture.
[0245] 4) The mixture obtained in step 3) was centrifuged and the obtained solid was dried in an oven at 80° C. overnight.
[0246] 5) The dried solid obtained in step 4) was calcined at 600° C. for 4 h to obtain SiO2@ZrO2, with a heating rate of 2° C. / min. The mass ratio of SiO2:ZrO2 was 1:0.4.
[0247] 6) Weighing the required drugs to prepare an aqueous solution in a molar ratio of nickel nitrate: cerium nitrate: citric acid = 1: 0.125: 1.35, wherein the nickel nitrate concentration is 1.3 mol / L; adding the prepared solution dropwise to the carrier obtained in step 5) by equal volume impregnation, sealing and standing for 24 hours, placing in an oven at 80° C. for 6 hours, and then drying at 120° C. overnight to obtain a dried product;
[0248] 7) The dried product obtained in step 6) was calcined at 600° C. for 4 h at a heating rate of 2° C. / min to obtain a catalyst precursor NiO-CeO2 / SiO2@ZrO2.
[0249] 8) The obtained catalyst precursor was placed in a reactor and reduced at 450°C for 1 h in 5% H2 / Ar with a flow rate of 10 mL / min and a heating rate of 1°C / min to obtain a catalyst Ni-CeO2 / SiO2@ZrO2 with a Ni mass fraction of 15%.
[0250] 9) Add 15000 mL / (g cat h) CO2 and hydrogen were introduced at a molar ratio of 1:4 to conduct CO2 methanation test. Under the pressure of 3Mpa, the catalytic performance of CO2 hydrogenation methanation reaction is as follows:
[0251] At 200°C, the CO2 conversion rate is 14.9%; at 350°C, the CO2 conversion rate is 91.7%; at 450°C, the CO2 conversion rate is 96.5%, and the CH4 selectivity at the above temperatures is 100%.
[0252] 10) Under the condition of 3Mpa pressure, the reactor was charged with a volume space velocity of 15000mL / (g cat h) introducing Fischer-Tropsch tail gas, wherein the tail gas composition is H2:CO2:CO:CH4:C2H6:C2H4:C3H8:C3H6:C4H 10 :C4H8:N2=5.5:1.0:0.5:0.5:0.05:0.013:0.03:0.06:0.013:0.03:3.7, at 200℃, the CO2 conversion rate is 12.9%, and the CO conversion rate is 51.8%; at 300℃, the CO2 conversion rate is 89.4%, and the CO conversion rate is 100%; at 400℃, the CO2 conversion rate is 97.9%, and the CO conversion rate is 100%.
[0253] It can be seen that all the embodiments involved in the present invention can show good catalytic performance in CO2 methanation and Fischer-Tropsch tail gas methanation reactions, and after undergoing long-term stability tests, the selectivity of the product remains stable without obvious deactivation, showing excellent stability and having extremely high application value.
[0254] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A ZrO2-coated SiO2-supported nickel catalyst, characterized in that: Its composition is Ni-MO x / SiO2@ZrO2; where: SiO2@ZrO2 is ZrO2 coated SiO2 material, used as a catalyst carrier; SiO2:ZrO2 in SiO2@ZrO2 is in a mass ratio of SiO2:1:(0.2-0.8); Ni is the active component of the catalyst, MO x MO is an additive added to the catalyst. x It is at least one of La2O3, CeO2, MgO, and CaO.
2. A ZrO2-coated SiO2-supported nickel catalyst according to claim 1, characterized in that: The mass fraction of Ni in the catalyst is 5 to 25%.
3. The ZrO2-coated SiO2-supported nickel catalyst according to claim 1, characterized in that: According to the molar ratio, Ni:MO x =1:(0~0.3).
4. A method for preparing a ZrO2-coated SiO2-supported nickel catalyst as claimed in any one of claims 1 to 3, characterized in that: The process includes the following: (1) dissolving zirconium nitrate in deionized water, adding glacial acetic acid and stirring to obtain a solution; (2) adding fumed silica to the solution obtained in step (1), and stirring with ultrasound until the fumed silica is completely dispersed to obtain a mixed solution; (3) slowly adding aqueous ammonia to the mixed solution obtained in step (2) until the pH value is 5.5 to 6.4, and then aging at a temperature of 60 to 90° C. to obtain a solid-liquid mixture; (4) centrifuging the solid-liquid mixture obtained in step (3) and drying the obtained solid; (5) calcining the dried solid in step (4) at 500-700° C. to obtain SiO2@ZrO2; (6) nickel nitrate, the corresponding nitrate of the auxiliary agent and citric acid are prepared into an aqueous solution, and the prepared aqueous solution is added dropwise to the SiO2@ZrO2 carrier obtained in step (5) by equal volume impregnation, and the mixture is sealed and allowed to stand at a temperature of 60 to 90° C., and dried to obtain a dried product; (7) calcining the dried product obtained in step (6) at 500-700° C. to obtain a catalyst precursor; (8) introducing reducing gas to reduce the catalyst precursor obtained in step (7), the reduction temperature being 450 to 700° C.; obtaining the catalyst Ni-MO x / SiO2@ZrO2.
5. The method for preparing a ZrO2-coated SiO2-supported nickel catalyst according to claim 4, characterized in that: The concentration of zirconium nitrate in the solution obtained in step (1) is 0.05-0.20 mol / L, and the concentration of glacial acetic acid is 0.6-2.4 mol / L.
6. The method for preparing a ZrO2-coated SiO2-supported nickel catalyst according to claim 4, characterized in that: The ammonia water feed rate in step (3) is 5 to 20 mL / h.
7. The method for preparing a ZrO2-coated SiO2-supported nickel catalyst according to claim 4, characterized in that: In step (6), the molar ratio of the sum of nickel nitrate and the corresponding nitrate of the auxiliary agent to citric acid is 1:(1-3).
8. A ZrO2-coated SiO2-supported nickel catalyst as claimed in any one of claims 1 to 2, applied to a CO2 methanation reaction or a Fischer-Tropsch tail gas methanation reaction.
9. The ZrO2-coated SiO2-supported nickel catalyst according to claim 8 is used in CO2 methanation reaction, characterized in that: The catalyst is added to a fixed bed reactor and, under the conditions of a temperature of 200-500°C and a pressure of 0.1-5 MPa, the reactor is charged with a volume space velocity of 5000-60000 mL / (g cat h) introducing carbon dioxide and hydrogen, wherein the molar ratio of carbon dioxide to hydrogen is 1:(1-5), to obtain the target product methane.
10. The ZrO2-coated SiO2-supported nickel catalyst according to claim 8 is applied to the Fischer-Tropsch tail gas methanation reaction, characterized in that: The catalyst is added to a fixed bed reactor and, under the conditions of a temperature of 200-500°C and a pressure of 0.1-5 MPa, the reactor is charged with a volume space velocity of 5000-60000 mL / (g cat h) introducing Fischer-Tropsch tail gas to obtain the target product methane.